Measuring customer satisfaction on the cleanliness of food premises using fuzzy conjoint analysis: A pilot test - Sook Yee Lim; Ummilia Balqis Harun; Abdul Rahman Gobil; Noor Afiqah Mustafa; Nur Azwanis Zahid; Syafinaz Amin-Nordin; Umi Kalsom Md. Ariffin; Tengku Zetty Maztura Tengku Jamaluddin; Nurul Azmawati Binti Mohamed @ Abd Aziz; Nor Afiah Mohd Zulkefli; Shamarina Shohaimi (Public Library of Science, 2024)
Indexed by WOS/SCOPUS/ERA